The Real Pleasure Of Freedom In Justin Lin's Fast And Furious 5 (2011): An Individual Psychological Approach - WINARNI, TUTI (2012)
Fast and Furious 5 (2011) by Justin Lin is an interesting and touchable is movie. The major problem of this study is how struggle of getting the real pleasure of freedom reflected in the movie Justin Lin's Fast and Furious 5 (2011) based on Individual Psychological Approach. Justin Lin is tries to create a character such as Dominic Toretto to encourage the reader to see how his life if it is seen from individual psychological approach. The researcher employs qualitative research method. In this method, the researcher uses two data resources namely primary and secondary data sources. The primary data source is the movie Justin Lin's Fast and Furious 5 (2011) itself. The secondary data source is the books about individual psychology and the other source related to the analysis. The method of data collection is descriptive technique. Both of data are combined to analysis the movie. All data are tightly bundled to support the idea. The results of this study shows that first; the structural elements of the movie present unity. It appears in the exposition, complication, climax, and resolution of the story. Second, the individual psychological analysis shows the striving of a fugitive who wants to build his new life by stealing money from the boss robber in Rio de Janeiro, Hernan Reyes. He does it well. He is able to enjoy his new life and getting freedom so that he does not need to live in prison. He spent the day in an Island with his girl.